Upaya Penanggulangan Gelandangan dan Pengemis yang dilakukan Rehabilitasi Sosial Dinas Sosial Kota Medan melalui Pengadaan Rumah Singgah - Salsabilah Syifa Siregar; Fajar Utama Ritonga; Bengkel Ginting (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
This article was created to look at the Medan City Government's efforts to reduce the number of people who need social welfare services, especially homeless people and beggars, based on Medan City Regional Regulation Number 6 of 2003 concerning the Prohibition of Homelessness and Begging in Medan City, which is implemented by the Social Rehabilitation sector at the Medan City Social Service. This journal discusses how to deal with Homelessness and Beggars through the provision of shelter homes established by the Rehabilitation sector at the Medan City Social Service. The function of the Social Rehabilitation sector is basically to carry out technical policy formulation, facilitation, coordination, monitoring and evaluation of social rehabilitation services. The provision of this halfway house is basically to carry out control in the city of Medan to reduce the number of homeless people and beggars in the city of Medan. The method for writing this journal is using the group work social work method.